2023
DOI: 10.21203/rs.3.rs-3438033/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seasonal extreme temperatures and short-term fine particulate matter increases child respiratory hospitalizations in a sparsely populated region of the intermountain western United States

Erin L. Landguth,
Jonathon Knudson,
Jon Graham
et al.

Abstract: Background Western Montana, USA, experiences complex air pollution patterns with predominant exposure sources from summer wildfire smoke and winter wood smoke. In addition, climate change related temperatures events are becoming more extreme and expected to contribute to increases in hospital admissions for a range of health outcomes. Few studies have evaluated these exposures (air pollution and temperature) that often occur simultaneously and may act synergistically on health. Methods We explored short-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 90 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…18 [1.20-3.97]), and for upper respiratory tract infections at a cumulative lag of 13 days (1.29 [1.07-1.57]). The strongest PM2.5 associations with hospital admissions for asthma and lower respiratory tract infections occurred during cold periods, in the winter [111]. These recent findings highlight the significance of proactive measures, including air quality monitoring and emergency plans.…”
Section: Childrenmentioning
confidence: 81%
See 1 more Smart Citation
“…18 [1.20-3.97]), and for upper respiratory tract infections at a cumulative lag of 13 days (1.29 [1.07-1.57]). The strongest PM2.5 associations with hospital admissions for asthma and lower respiratory tract infections occurred during cold periods, in the winter [111]. These recent findings highlight the significance of proactive measures, including air quality monitoring and emergency plans.…”
Section: Childrenmentioning
confidence: 81%
“…Few studies have evaluated the complex effects of exposures to wildfire smoke, air pollution, and temperature that may act synergistically on health. Landguth et al [111] studied exposure to air pollution and temperature on the risk of hospitalizations and found that short-term increases in PM2.5 were associated with elevated odds of hospitalizations for asthma at lag 7-13 days (1.87 [1.17-2.97]), for lower respiratory tract infections at lag 6-12 days (2. 18 [1.20-3.97]), and for upper respiratory tract infections at a cumulative lag of 13 days (1.29 [1.07-1.57]).…”
Section: Childrenmentioning
confidence: 99%